2023
DOI: 10.1177/0271678x231167946
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of the detrimental effects of social isolation on ischemic cerebral injury and stroke-associated pneumonia by inhibiting small intestinal γδ T-cell migration into the brain and lung

Abstract: Social isolation (ISO) is associated with an increased risk and poor outcomes of ischemic stroke. However, the roles and mechanisms of ISO in stroke-associated pneumonia (SAP) remain unclear. Adult male mice were single- or pair-housed with an ovariectomized female mouse and then subjected to transient middle cerebral artery occlusion. Isolated mice were treated with the natriuretic peptide receptor A antagonist A71915 or anti-gamma-delta (γδ) TCR monoclonal antibody, whereas pair-housed mice were treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 104 publications
(135 reference statements)
0
4
0
Order By: Relevance
“…For in vivo tracing of intestinal immune cells, photoconversion was performed, as previously described 41 . Brie y, after completion of CLP or sham surgery, the small intestine of Kaede-transgenic mice were exposed to a 405-nm laser for a duration of 10 min, while ensuring the surrounding tissue was shielded from light using aluminum foil.…”
Section: Kaede Photoconversionmentioning
confidence: 99%
See 2 more Smart Citations
“…For in vivo tracing of intestinal immune cells, photoconversion was performed, as previously described 41 . Brie y, after completion of CLP or sham surgery, the small intestine of Kaede-transgenic mice were exposed to a 405-nm laser for a duration of 10 min, while ensuring the surrounding tissue was shielded from light using aluminum foil.…”
Section: Kaede Photoconversionmentioning
confidence: 99%
“…Cell suspensions from lung, small intestine, mesenteric lymph nodes (MLNs), blood and spleen were prepared as previously reported 41 . Cells were blocked with 5 ng µl -1 of anti-CD16/CD32 antibody for 10 min at 4 ℃ and stained with the appropriate antibodies.…”
Section: Facs Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, antibiotic-induced microbiome depletion could reduce acute lung injury after lipopolysaccharide administration [ 136 ]. Another recent study demonstrated that small intestinal γδ T-cell migration into the lung and brain plays a role in stroke-associated pneumonia in mice [ 56 ]. Given the emerging recognition of the lung–brain axis [ 135 , 137 , 138 ], it becomes increasingly compelling to explore whether the lung microbiota plays a role in the development and progression of neuropsychiatric disorders.…”
Section: Lung Microbiotamentioning
confidence: 99%